Application as assistive technology: a inclusion of environmental science teaching in special education - José Macio Rodrigues Ribeiro (Universidade Estadual de Alagoas, 2023)
Educational inclusion has been overcoming barriers in the face of the challenge of achieving equal education for all. Disabled children must live with other typical children from an early age, this brings benefits not only to themselves, but also to other children at school. With the objective of developing an application as an assistive technology tool in the teaching of Environmental Sciences, this research finds in its path several forms of reflection on education, especially in the Teaching of Environmental Sciences, going through some themes to reach the utopia that is the inclusion of inclusive education students in the school in a cooperative way, with the management of natural resources involved in a vegetable garden, with activities aimed at sustainable actions to improve the environment in which they live and their well-being. Based on an applied research of an exploratory nature with a qualitative approach developed at Escola Cônego Eugênio Vilanova, Gravatá- PE, the application "Minha hortinha" developed on the Fábrica de Applications platform provides content and interactivity about gardening, recycling, water saving, literacy and inclusion. And since inclusive education in schools has been a challenge for teachers, who mostly have difficulties working with students with global developmental disorders, high abilities and disabilities, with a limitation of digital tools, the developed application brings in an interdisciplinary way, various activities adapted for students of Elementary School - Early Years.